Profile of students ocean literacy at senior high school in Mataram - Lalu Hasan Nasiruddin Zohri; Irmayani Irmayani; Yufika Dewi Muksin; Abdul Syukur; Jamaluddin Jamaluddin (Jurnal Pijar Mipa, 2021)
Ocean literacy is knowledge about the biophysical and ecological aspects of the ocean that have relevance to the topic of biology learning. This study aims to classify the profiles on ecosystem topics of t he ocean literacy of the high school students of SMA 1 Mataram. This study uses an observational approach with a purposive sampling technique, while the data analysis used is descriptive statistical analysis. Furthermore, the samples of this study are 186 of 848 students. The classification of studentsÃ¢â¬â¢ literacy on ocean ecological aspects in SMA 1 Mataram are: the percentage of correct answers on indicator 1 is 41.55%, indicator 2 is 68.55%, and indicator 3 is 41.40%. This study concludes that high school students at the study site have not had sufficient knowledge about ocean ecology. However, some materials, such as ocean ecosystems, can be a source of learning to improve students' literacy about ocean ecologies, such as tropical structures in a coral reef, seagrass, and mangrove ecosystems. Therefore, it is necessary to innovate learning resources from ocean environments, especially schools close to the sea, such as a high school in the study site and other high schools in other places